Fulfilling a social mission: examining practice locations of residency graduates over two decades - Tim Dubé; Matthieu Touchette; Linda Bergeron; Mariem Fourati; Cassandra Barber; Christina St-Onge (Canadian Medical Education Journal)
Background: Medical schools play a critical role in shaping the physician workforce. Tracking the practice locations of medical graduates is essential for addressing healthcare disparities and workforce shortages in underserved regions. This study examines the geographic distribution of residency graduates from a Canadian francophone university, aligning their practice locations with the university’s social accountability mandate.